2002
DOI: 10.1097/00001665-200201000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Osteogenesis in Pierre Robin Sequence and Related Respiratory Problems in Children

Abstract: Mandibular distraction is a safe and reliable procedure for treating patients with obstructive sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 13 publications
0
71
0
5
Order By: Relevance
“…Other series have attained similar results. In 2002, Ortiz-Monasterio et al 10 (n=4) and Denny and Kalantarian 6 (n=5) reported on neonates (aged Ͻ1 month) with PRS and severe upper airway obstruction, all of whom were able to avoid tracheotomy after mandibular DOG.…”
Section: Commentmentioning
confidence: 99%
“…Other series have attained similar results. In 2002, Ortiz-Monasterio et al 10 (n=4) and Denny and Kalantarian 6 (n=5) reported on neonates (aged Ͻ1 month) with PRS and severe upper airway obstruction, all of whom were able to avoid tracheotomy after mandibular DOG.…”
Section: Commentmentioning
confidence: 99%
“…In 2001, Denny et al [10] demonstrated that mandibular advancement through distraction osteogenesis could improve airway dimensions and result in decannulation in tracheostomy-dependent children. Monasterio [11] and Sidman et al [12], also showed excellent results using distraction to prevent the need for tracheostomy in neonates and children with mandibular hypoplasia with severe tongue-based obstruction.…”
Section: Discussionmentioning
confidence: 95%
“…Monasterio [9] and Sidman et al [10], also showed excellent results using distraction to prevent the need for tracheostomy in neonates and children with mandibular hypoplasia with severe tongue-based obstruction. All of these authors used external distraction devices.…”
Section: Discussionmentioning
confidence: 95%